STUDI KOMPARATIF PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD DAN TIPE JIGSAW DALAM MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA : Studi Eksperimen pada Mata Pelajaran Ekonomi Siswa Kelas X SMA Negeri 1 Cilegon - Yulianti, Wahyuni (2012)
Research on the comparative study of the use of cooperative learning type STAD and Jigsaw Study aims to identify differences in the activity and student learning outcomes. Except, to know the different learning outcomes and learning activities of students between classes given treatment using STAD cooperative learning type with a given class treatment using the Jigsaw cooperative learning type on economic subjects. The research method used was quasi-experimental methods, with subjects consisted of two classes, class X.7 (STAD class) and X.8 (Jigsaw class). Data collection is done by written test and observation sheets filled by the observer or subject teachers concerned. Data processing is performed with independent samples t-test using Microsoft Office Excel 2007. Based on the results of the study indicate that there are differences in the activity and student learning outcomes in the classroom STAD before and after treatment. For Jigsaw class, there are differences in student learning activities before and after treatment. However, there was no difference in learning outcomes at Jigsaw classroom before and after treatment. So it can be said that the use of cooperative learning STAD type and Jigsaw to increase students learning activities, and the scarcity of material and human needs use type STAD cooperative learning better able to improve student learning outcomes